KORELASI ANTARA MOTIVASI BELAJAR DAN PENGETAHUAN KKPI DENGAN PRESTASI BELAJAR DASAR KEJURUAN DI SMK ISLAM YOGYAKARTA TAHUN AJARAN 2013/2014 - Randi Setioko; Samsul Hadi (Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of the study ( 1 ) to determine whether there is a correlation betweenÂ motivation of learning and knowledge KKPI with achievement learning of base profession in Islamic vocational school of Yogyakarta academic year 2013/2014, ( 2 ) to determine whether there is a correlation between motivation of learning and achievement in learning in Islamic vocational school of Yogyakarta academic year 2013/2014, ( 3 ) to determine whether there is a correlation between knowledge KKPI with achievement learning of base profession in Islamic vocational school of Yogyakarta academic year 2013/2014.This research was conducted in Islamic vocational school of Yogyakarta academic year 2013/2014. The population in this study were all students of class X TO which total 30 students and this study used a sampling saturated or study populations so that the entire population were sampled. This research is correlational and ex post facto categorized. With the questionnaire data collection techniques, and documentation about the test. The validity of the items were obtained from the product moment correlation. About the reliability obtained with the formula stated alpha and reliable. Before the data were analyzed first tested the prerequisite analysis is normality test, test and test intercorrelations linearity. Analysis using multiple regression analysis and partial correlation.Based on the analysis of the results obtained the following results. ( 1 ) there is a positive and significant correlation between motivation to learn ( X1 ) and knowledge KKPI ( X2 ) together with achievement learning of base profession ( Y ) ; ( 2 ) there is a positive and significant correlation between motivation to learn ( X1 ) with basic vocational learning achievement ( Y ) ; ( 3 ) there is a positive and significant correlation between knowledge KKPI ( X2 ) with achievement learning of base profession ( Y ).